Difference of Fourth Powers of Cosine and Sine
Jump to navigation
Jump to search
Theorem
- $\sin^4 x - \cos^4 x = \sin^2 x - \cos^2 x$
where $\sin$ and $\cos$ denote sine and cosine respectively.
Proof 1
\(\ds \sin^4 x - \cos^4 x\) | \(=\) | \(\ds \sin^2 x \left({1 - \cos^2 x}\right) - \cos^2 x \left({1 - \sin^2 x}\right)\) | Sum of Squares of Sine and Cosine | |||||||||||
\(\ds \) | \(=\) | \(\ds \sin^2 x - \sin^2 x \ \cos^2 x - \cos^2 x + \sin^2 x \ \cos^2 x\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sin^2 x - \cos^2 x\) |
$\blacksquare$
Proof 2
\(\ds \sin^2 x - \cos^2 x\) | \(=\) | \(\ds \left({\sin^2 x - \cos^2 x}\right) \left({\sin^2 x + \cos^2 x}\right)\) | Sum of Squares of Sine and Cosine | |||||||||||
\(\ds \) | \(=\) | \(\ds \sin^4 x - \cos^4 x\) | Difference of Two Squares |
$\blacksquare$